Bahasa Indonesia . - Fenny Anita; Nurul Mustaqimmah; Rosalina A Muis (JURNAL PENDIDIKAN ROKANIA, 2023)
Cancer is not only a health problem for adults; it is also a major health problem for children. The pediatric oncology polyclinic in Riau Province, particularly in Pekanbaru City, recorded 1,918 cancer patients. Generally, cancer sufferers are more closed to themselves, withdraw from the environment, and reject what has happened to them, so that most cancer sufferers surrender, lose motivation, and lose self-confidence. Empathic communication can help cancer survivors motivate, understand, and understand their feelings and attitudes, as well as their hopes and desires for the future. As a result, parental empathic communication is required. The purpose of this study was to determine the empathic communication between parents and children with cancer at YKAKI Pekanbaru. This study involved three informants who were parents of children with cancer and one support respondent. Methods of data collection using interviews, observations, and documentation techniques The results of this study indicate that empathetic communication between parents and children can take the form of prioritizing communication, providing motivation to children, showing patience and sincerity, influencing children's responses, and growing a sense of comfort in children. All findings from this study show forms of empathic communication between parents and children with cancer at YKAKI Pekanbaru City.